Digital Economy and Carbon Emissions Reduction: The Mediating Impact of Industrial Structure Transformation - Wang Kai; Aza Azlina Md Kassim (Technium Social Sciences Journal, 2025)
This study investigates the impact of the digital economy on per capita carbon emissions across 30 Chinese provinces from 2013 to 2022, with a specific focus on the mediating role of industrial structure transformation. A composite index of digital economy development is constructed using the entropy weight method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The Three-Stage Least Squares (3SLS) method is applied to examine both direct and indirect effects. The results show that a 0.119-unit increase in the digital economy index leads to a reduction of approximately 25,900 tons in per capita carbon emissions, representing around 21.8% of the sample mean. Furthermore, the digital economy significantly reduces emissions by promoting the upgrading of industrial structures. These findings provide valuable insights into the mechanisms through which digitalization supports low-carbon development and offer important policy implications for achieving carbon reduction targets.